MEGA-CHONDRULES AND LARGE, IGNEOUS-TEXTURED CLASTS IN JULESBERG (L3) AND OTHER ORDINARY CHONDRITES: VAPOR-FRACTIONATION, SHOCK-MELTING, AND CHONDRULE FORMATION - Ruzicka A.; Snyder G.A.; Taylor L.A. (My University, 1998)
A petrographic-microprobe study of large, metal-poor, igneous-textured objects in Julesberg (L3) and other ordinary chondrites suggests that they can be classified into two petrographic types: megachondrules and large lithic clasts; and into two chemical types: Na-poor and Na-rich.Mega-chondrules show textural evidence of having solidified as freely-floating melt droplets, whereas lithic clasts formed by the fragmentation of larger objects, possibly still larger mega-chondrules. Barred-olivine or barred-olivine-pyroxene textures are most common for mega-chondrules, whereas a variety of textures occur in large lithic clasts. The two petrographic types cannot be distinguished on the basis of modal, bulk, or phase compositions.Sodium-poor objects are characterized by (1) plagioclase or glass with mainly bytownite composition (An70-90 typical), (2) subchondritic Na/Al ratios and typically subchondritic volatile-element (Na, K, and Mn) abundances, and (3) bulk-chemical trends that resemble those expected for vapor-fractionation processes. Some Na-poor objects may have formed by the melting of precursors that formed as condensates or vaporization residues; others may have formed by the melting of precursors that formed by fractional condensation or fractional vaporization. Following vapor-fractionation, Na-poor objects or their precursors appear to have reequilibrated at lower temperatures, which raised the bulk Na content of the objects, but not to the levels seen in Na-rich objects. Enrichments of Fe2+, Na, K, and P on the margins of some Na-poor objects suggest that they partly reacted with volatile-rich surrounding, both before and after brecciation. Sodium-rich objects are characterized by (1) plagioclase or glass with oligoclase or albite composition (An2-25), (2) roughly chondritic Na/Al ratios and volatile-element (Na, K, Mn) abundances, and (3) bulk-chemical trends similar to those shown by melt-pocket glasses in ordinary chondrites. Sodium-rich melt objects could have formed by the shock-melting of chondritic precursors. Feldspathic compositions for some Na-rich melt objects can be explained by preferential shock-melting of feldspar or feldspathic glass in chondritic target materials.Literature data imply that the same two chemical populations of objects, Na-poor and Na-rich, occur among smaller, normal-sized chondrules in Type 3 ordinary chondrites, suggesting that the same processes that affected large melt objects also affected chondrules.